2011
DOI: 10.1093/infdis/jir098
|View full text |Cite
|
Sign up to set email alerts
|

Two Case Studies of Modified Measles in Vaccinated Physicians Exposed to Primary Measles Cases: High Risk of Infection But Low Risk of Transmission

Abstract: In 2009, measles outbreaks in Pennsylvania and Virginia resulted in the exposure and apparent infection of 2 physicians, both of whom had a documented history of vaccination with >2 doses of measles-mumps-rubella vaccine. These physicians were suspected of having been infected with measles after treating patients who subsequently received a diagnosis of measles. The clinical presentation was nonclassical in regard to progression, duration, and severity. It is hypothesized that the 2 physicians mounted vigorous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
97
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 130 publications
(109 citation statements)
references
References 10 publications
10
97
0
2
Order By: Relevance
“…This is in keeping with an attenuation of clinical severity in immunized hosts that is recognized in other vaccine-preventable diseases (24)(25)(26).…”
Section: Figure 1: Literature Search Resultssupporting
confidence: 68%
“…This is in keeping with an attenuation of clinical severity in immunized hosts that is recognized in other vaccine-preventable diseases (24)(25)(26).…”
Section: Figure 1: Literature Search Resultssupporting
confidence: 68%
“…38 , 39 Their ability to transmit virus, however, is thought to be greatly diminished, as subsequent spread of measles from a person with prior immunity has rarely been documented. 38 , 40 , 41 Because primary versus secondary vaccine failure cases cannot be readily distinguished without specialized testing and cases with a past immunologic response to measles might be contagious, 38 any person with confirmed measles, regardless of vaccination status, is recommended to be isolated for the duration of the infectious period. 1-4 (Of note, transmission from previously immune individuals is of great interest and has important implications for sustaining elimination; studying such transmission requires clinical specimens and specialized laboratory investigations.…”
Section: Containment Strategies — Guidance Evidence Challenges Andmentioning
confidence: 99%
“…3). Moreover, we considered that the two associates developing M-Me were not related to the measles transmission because preceding studies indicated that the transmissibility of M-Me was low (12,13).…”
Section: For Detecting Measles Patients Promptly Molecular Amplificamentioning
confidence: 99%
“…These patients could be sources of transmission even though the risk is low (12)(13)(14). In order to prevent measles transmission and outbreaks, cases of M-Me should be adequately diagnosed, as should cases of T-Me.…”
Section: Introductionmentioning
confidence: 99%